Clinical Characteristics, Laboratory Profiles, And Treatment Modalities for Familial Hypercholesterolemia in Egypt. (8th October 2021) - Reda, Ashraf; Bendary, Ahmed; Elserafy, Ahmed Shawky; Ashraf, Mohamed; Dawood, Ehab; Emil, Sameh; Elbahry, Atef; Sanad, Osama; Bendary, Mohamed; Elhadidy, Amro; Rafla, Samir; Tabl, Mohamed Abdelshafy; et al.
Abstract: Aims: The aim of the Familial Hypercholesterolemia Research Collaboration (FHRC) is to collect date about the clinical, laboratory phenotypes, and treatment strategies of patients with FH all over the world. We present the Egyptian data of this international registry. Methods and Results: An online electronic case report form (e-CRF) was prepared to collect data matching the protocol of the FHSC of the European Atherosclerosis Soci- ety (EAS). From August 2017 to March 2021, a total of 228 cases with FH (46% males, mean age 48 ± 14 years) were enrolled. About 71% of whom came from urban areas. The mean Body Mass Index (BMI) was 30 ± 4.9 kg/m2. The most commonly reported concomitant risk factor was hypertension (39%), followed by smoking (22%), and then DM (18%). Median time from diagnosis to enrolment was 7 (range 0.5-20) years. The vast majority (99.1%) were diagnosed based on the Dutch Lipid Clinic criteria, with 14%, 11% and 75% in the definite, probable, and possible categories respectively. Genetic test was performed in only 1 patient, in which the defect was heterozygous FH (defective ApoB). Mean baseline levels for total cholesterol was 316±86 mg/dl, median (ranges) for triglycerides was 190 (38-1400) mg/dl, for LDL-C was 237±77 mg/dl and for HDL-C was 47±14 mg/dl. Importantly, the mean Lp(a) was 42±12 mg/dl. All but one patient received lipid lowering therapy. Statins were prescribed in 226 out of 228 patients enrolled (99.1%). Statin prescriptions were equally distributed between Atorvastatin and Rosuvastatin (41% for each). Forty five percent received monotherapy and 56% received combination therapy (most commonly with Ezetimibe [55.7%], then with Fibrates [7.9%], then with proprotein con- vertase subtilisin/kexin type 9 (PCSK-9 inhibitors) [2.6%], and finally with Omega-3 fatty acids [0.9%]). Only one patient received lipoprotein apheresis. Conclusion: The Egyptian part of the FHRC, to the best of our knowledge, is the first FH registry in Egypt. Our data show that the e-CRF system is feasible and reliable. The phenotype of enrolled FH cases showed higher female preponderance, very high lipoprotein levels, and unfortunately inadequate therapeutic interventions (with un- derutilization of PCSK-9 inhibitors). This is a call to action in order to mitigate these management gaps for this high-risk group.